2014
DOI: 10.1016/j.echo.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Implantable Transvenous Device Lead Location on Severity of Tricuspid Regurgitation

Abstract: Background Implantable device leads can cause tricuspid regurgitation (TR) when they interfere with leaflet motion. The aim of this study was to determine whether lead-leaflet interference is associated with TR severity, independent of other causative factors of functional TR. Methods A total of 100 patients who underwent transthoracic two-dimensional and three-dimensional (3D) echocardiography of the tricuspid valve before and after lead placement were studied. Lead position was classified on 3D echocardiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 30 publications
4
53
0
1
Order By: Relevance
“…28 However, lead location has not been shown to affect tricuspid regurgitation 29 but use of 3D echocardiography to evaluate the etiology of tricuspid regurgitation may be useful. 29,30 3D echocardiography may also aid in determining torque force of the patients ventricle, 31 unfortunately this sophisticated imaging was not performed. Furthermore, subcutaneous ICD (S-ICD) may eliminate the risk of tricuspid regurgitation associated with endovascular leads.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, lead location has not been shown to affect tricuspid regurgitation 29 but use of 3D echocardiography to evaluate the etiology of tricuspid regurgitation may be useful. 29,30 3D echocardiography may also aid in determining torque force of the patients ventricle, 31 unfortunately this sophisticated imaging was not performed. Furthermore, subcutaneous ICD (S-ICD) may eliminate the risk of tricuspid regurgitation associated with endovascular leads.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple case reports have described patients with intracardiac devices in whom adverse lead‐TV interactions were well described with the addition of 3D assessment . Data from retrospective case series suggest that in 74–94% of 2D studies with adequate windows, 3D images are able to clearly define the position of a device lead as it passes through the level of the tricuspid annulus, with a high degree of agreement between interpreters . Although based primarily on retrospective data, clarifying lead positioning has significant implications: leads positioned over and/or pinning a leaflet (predominantly septal or posterior) are predictive of TR, as opposed to leads which pass through the middle of the valve or in the commissures (predominantly posteroseptal) .…”
Section: Diagnosismentioning
confidence: 99%
“…Data from retrospective case series suggest that in 74–94% of 2D studies with adequate windows, 3D images are able to clearly define the position of a device lead as it passes through the level of the tricuspid annulus, with a high degree of agreement between interpreters . Although based primarily on retrospective data, clarifying lead positioning has significant implications: leads positioned over and/or pinning a leaflet (predominantly septal or posterior) are predictive of TR, as opposed to leads which pass through the middle of the valve or in the commissures (predominantly posteroseptal) . This modality has even been used to assess the degree of fibrosis involving the lead and leaflet tissue (confirmed by surgery), which has significant implications for the options for lead extractions …”
Section: Diagnosismentioning
confidence: 99%
“…Multiple publications have reported the usefulness of 3D echocardiography for detecting the location of the lead and its association with significant TR. [155][156][157][158] In one of those studies, 45 of 100 patients showed device lead TV leaflet interference. The septal leaflet was the that provides an accurate and reliable quantitative assessment of AS.…”
Section: Aortic Valvementioning
confidence: 99%
“…The authors concluded that lead-leaflet interference as seen on 3D echocardiography is associated with TR after device lead placement, suggesting that 3D echocardiography should be used to assess lead interference in patients with significant TR. 156 Fukuda et al used 3D echocardiography to reveal that one of the causes of secondary or functional TR was dilation and flattening of the tricuspid annulus. 159 In another clinical 3D echocardiographic study of 54 patients with various degrees of functional TR, septal leaflet tethering, septal-lateral annular dilatation, and the severity of pulmonary hypertension were the main determinants of TR severity.…”
Section: Aortic Valvementioning
confidence: 99%